The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.7326/0003-4819-148-2-200801150-00192
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Comparative Effectiveness and Harms of Disease-Modifying Medications for Rheumatoid Arthritis

Abstract: Limited available comparative evidence does not support one monotherapy over another for adults with rheumatoid arthritis. Although combination therapy is more effective for patients whose monotherapy fails, the evidence is insufficient to draw firm conclusions about whether one combination or treatment strategy is better than another or is the best treatment for early rheumatoid arthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
153
1
13

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(171 citation statements)
references
References 59 publications
3
153
1
13
Order By: Relevance
“…In 1993, when this study was begun, the clinical use of methotrexate in RA was far rarer than today, and there were no studies showing its superiority compared with other DMARDs. Even a recent review (29) found no evidence of the superiority of methotrexate in comparison with other DMARDs in terms of clinical efficacy. In our study, the single-DMARD strategy was not tied to sulfasalazine but to a strategy of using 1 DMARD at a time.…”
Section: Discussionmentioning
confidence: 98%
“…In 1993, when this study was begun, the clinical use of methotrexate in RA was far rarer than today, and there were no studies showing its superiority compared with other DMARDs. Even a recent review (29) found no evidence of the superiority of methotrexate in comparison with other DMARDs in terms of clinical efficacy. In our study, the single-DMARD strategy was not tied to sulfasalazine but to a strategy of using 1 DMARD at a time.…”
Section: Discussionmentioning
confidence: 98%
“…In 2012, the American College of Rheumatology updated its recommendations for the treatment of RA through a systematic review of the literature and scientific evidence, and an aggressive therapeutic approach to RA was championed (3). As compared to monotherapy with methotrexate, a synthetic disease-modifying antirheumatic drug (DMARD), the use of biologic DMARDs or the combination of biologic DMARDs plus methotrexate leads to better radiographic outcomes, greater functional independence, and higher rates of remission (4). Moreover, the improvement of healthrelated quality of life years among patients receiving biologic DMARDs has also been reported (5).…”
Section: Introductionmentioning
confidence: 99%
“…20 Reported as incidence rates, the most common adverse events observed in observational studies on biologic agents were diarrhea (7%-18%), headache (12%-18%), nausea (8%-20%), rhinitis (8%-18%), injection site reactions (19%-56%), and upper respiratory tract infections (9%-24%). 10 Comparisons of TNF-alpha inhibitors generally indicated no significant differences in rates of adverse events, including serious infections, and no increases in rates over time. A systematic review indicated higher rates of injection site reactions in patients using anakinra compared with adalimumab or etanercept.…”
Section: Comparisons Of Biologic Agents Used As Monotherapymentioning
confidence: 96%
“…9 Conducted by the RTI-University of North Carolina EPC, the review included 42 head-to-head trials and 58 observational studies on RA therapies. 10 Published studies were identified and obtained through comprehensive database searches covering the period from 1980 through September 2007. The key clinical questions that guided the review are summarized as follows:…”
Section: Ahrq's 2007 Cer On Rheumatoid Arthritis Therapiesmentioning
confidence: 99%